The relationship between diet and the incidence of diabetes mellitus in the working area of the Medan Sunggal Health Centre - Hastuti, Mona; Tarigan, Rinawati (Journal of Midwifery and Nursing, 2024)
Diabetes is a disease caused by disturbances in the absorption of blood sugar by the body, thus making its levels in the blood high. Indonesia ranks 4th largest in the number of people with Diabetes Mellitus in the world. In 2019 there were around 5.6 million Indonesians with diabetes and was the sixth cause of death in Indonesia in the non-communicable disease category. This study aims to determine the relationship between lifestyle and the occurrence of diabetes mellitus. This research is a type of research using random sampling method. This research was conducted at Medan Sunggal Health Centre and the research time was in October 2022. The population in this study were all patients who sought treatment at the Puskesmas as many as 62 people and the sample size in this study was 54 people. The sampling technique used non-random sampling by accidental sampling. This study uses primary data and secondary data. The results of this study indicate that there is a relationship between diet and diabetes mellitus disease where the pvalue of diet = 0.008 (> 0.05). Based on the results of the study it can be concluded that there is a relationship between diet and the incidence of diabetes mellitus. It is recommended that respondents continue to strive to increase knowledge about diet, increase compliance in living a healthy life.